AKTIVITAS HUMAS DPRD KOTA PALU SEBAGAI MEDIATOR ASPIRASI MASYARAKAT - Alem Febri Sonni; Ratmila Riandani; Andi Alimuddin Unde; Abdul Gafar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2021)
The aim of this study were (1) to find out how the public relations activities of Palu City Council in running the function as mediator aspirations of the community, and (2) to find out what are the inhibitors and supporter of public relations activities in its function as mediator aspirations of the people. This type of research is descriptive qualitative, that describe, explain and define about the object under study is based on interviews and observations obtained in a study of public relations officials and officials of Palu City Council. The results of this study indicate that the activity of the Public Relations Council of Palu in its function as a mediator by way of mediating the public officials of Parliament linked to the existing problems and the other functions of public relations City Council Palu also conducts publicity activities The factors supporting and inhibiting Public Relations Activities Palu City Council as a mediator aspirations of the people which is understanding public relations officer with their function and of course a good cooperation between members of the public relations is very helpful in fulfilled public relations function. While the limiting factor is the lack of human resources (HR) and facilities that support the activities of PR in publish and disseminate information.